Democracy and cyberconflict: how regime type affects state-sponsored cyberattacks. Issue 1 (2nd January 2022) - Hunter, Lance Y.; Albert, Craig D.; Garrett, Eric; Rutland, Josh
ABSTRACT : A large body of research in international relations has focused on the relationship between regime type (i.e., the degree a nation is democratic or authoritarian) and traditional military conflict between states. However, to date, no research has examined how regime type affects conflict in the cyber domain. Thus, we attempt to analyze the effect regime type has on the initiation of state-sponsored cyberattacks. We examine 143 states from 2005 - 2013 utilizing cyber data on known state-sponsored cyberattacks taken from the Council on Foreign Relations Cyber Operations Tracker dataset (CFR-COTD) and economic, political, military, and social data collected by the authors. In conducting a cross-sectional, time series analysis we find that democratic institutions have a pacifying effect on the initiation of state-sponsored cyberattacks.